Influence of ligation method on friction resistance of lingual brackets with different second-order angulations: An in vitro study - Pereira, Graziane Olímpio; Gimenez, Carla Maria Melleiro [UNESP]; Prieto, Lucas; Do Lago Prieto, Marcos Gabriel; Basting, Roberta Tarkany (FapUNIFESP (SciELO), 2016)
Objective: To evaluate stainless steel archwire static friction in active and passive self-ligating lingual and conventional brackets with secondorder angulations. Methods: Two conventional lingual brackets for canines (STb light/Ormco; PSWb/Tecnident), and two self-ligating brackets, one active (In-Ovation L/GAC) and the other passive (3D/ Forestadent), were evaluated. A stainless steel archwire was used at 0°, 3° and 5° angulations. Metal ligatures, conventional elastic ligatures, and low friction elastic ligatures were also tested. A universal testing machine applied friction between brackets and wires, simulating sliding mechanics, to produce 2-mm sliding at 3 mm/minute speed. Results: Two-way analysis of variance demonstrated a significant effect of the interaction between brackets and angulations (p < 0.001). Tukey test indicated that the highest frictional resistance values were observed at 5° angulation for In-Ovation L, PSWb bracket with non conventional ligature, and STb bracket with metal ligature. As for 3D, PSWb with conventional or metal ligatures, and STb brackets with non conventional ligature, showed significantly lower static frictional resistance with 0° angulation. At 0° angulation, STb brackets with metal ties, In-Ovation L brackets and 3D brackets had the lowest frictional resistance. Conclusions: As the angulation increased from 0° to 3°, static friction resistance increased. When angulation increased from 3° to 5°, static friction resistance increased or remained the same. Self-ligating 3D and In-Ovation L brackets, as well as conventional STb brackets, seem to be the best option when sliding mechanics is used to perform lingual orthodontic treatment.
Keywords: Friction; Ligation; Orthodontic brackets